Nonlinear Optical Properties of Novel Forms of Enriched Carbon Disulfide - Edziah, Raymond (My University, 2010)
The ultimate goal of designing molecules with large third-order nonlinearities is to incorporate them into optical switching and limiting devices. To achieve this, the molecules must have large and fast optical nonlinearities. We undertook picosecond and femtosecond studies of carbon disulfide (CS2) enriched with sulfur, selenium, cadmium telluride nanoparticles and 2-methyl-4-nitroaniline (MNA) for enhanced optical nonlinearities, using the Z-scan technique. In this method, a sample is scanned along the optic axis (chosen as the z- direction) in the focal region of a single focused laser beam. The intensity transmitted through the region with an aperture (nonlinear refraction) or without an aperture (nonlinear absorption) in the far field is recorded as a function of the sample position. Due to the high intensity of the electromagnetic field in this region, the sample tends to behave as a lens of variable focal length and can focus or defocus the beam depending on the sign of the nonlinearity. Our measurements with a 130-fs source indicate that the nonlinear absorption coefficient of CS2 was enhanced by more than two orders of magnitude (over pure CS2) through sulfur and selenium enrichment; while their nonlinear refractive indices experienced minimal change. Enhanced nonlinearities of enriched CS2 molecules may be harnessed for sensor applications.
Keywords: carbon disulfide; enriched carbon disulfide; nonliear absorption coefficient; optical limiters; optical limiting; Z-scan